2018
DOI: 10.1016/s2214-109x(18)30002-0
|View full text |Cite
|
Sign up to set email alerts
|

Dominant modifiable risk factors for stroke in Ghana and Nigeria (SIREN): a case-control study

Abstract: Summary Background Sub-Saharan Africa has the highest incidence, prevalence, and fatality from stroke globally. Yet, only little information about context-specific risk factors for prioritising interventions to reduce the stroke burden in sub-Saharan Africa is available. We aimed to identify and characterise the effect of the top modifiable risk factors for stroke in sub-Saharan Africa. Methods The Stroke Investigative Research and Educational Network (SIREN) study is a multicentre, case-control study done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
186
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 215 publications
(216 citation statements)
references
References 29 publications
(49 reference statements)
10
186
2
5
Order By: Relevance
“…On a much broader scale, our previous report shows a highly prevalent but poorly controlled hypertension rate in the general population based on evidence gleaned from our HIV-negative sample. 22 This may explain why we found that HIV per se was not to be independently associated with stroke occurrence in a low endemic country such as Ghana, 44 although the burden of stroke and poor outcomes continue to rise in the subregion [45][46][47][48] due to a myriad of factors hampering the control of key CVD risk factors. 49…”
Section: Discussionmentioning
confidence: 94%
“…On a much broader scale, our previous report shows a highly prevalent but poorly controlled hypertension rate in the general population based on evidence gleaned from our HIV-negative sample. 22 This may explain why we found that HIV per se was not to be independently associated with stroke occurrence in a low endemic country such as Ghana, 44 although the burden of stroke and poor outcomes continue to rise in the subregion [45][46][47][48] due to a myriad of factors hampering the control of key CVD risk factors. 49…”
Section: Discussionmentioning
confidence: 94%
“…The number of deaths from stroke in SSA have increased by nearly 50% in past three decades [2,11,68]. Stroke tends to affect the younger productive workforce in SSA compared to the developed world [6], and the mean age at death from stroke in SSA also the lowest among all low-to middle-income countries [2,11,66]. Community-based studies in Africa have revealed age-standardized (to the WHO world population) annual stroke incidence rates of up to 316 per 100,000 population, and age-standardized prevalence rates of up to 981 per 100,000 [67,68].…”
Section: Stroke (Cerebrovascular Disease)mentioning
confidence: 99%
“…A few studies have demonstrated overall positive patient outcomes following acute stroke care interventions in Africa [71]. Given that hypertension is the single most important preventable risk factor for stroke in SSA [6,66], its optimal control should be the main focus to help reduce stroke occurrence.…”
Section: Stroke (Cerebrovascular Disease)mentioning
confidence: 99%
See 1 more Smart Citation
“…This observed mortality is somewhat similar to that of 44% and 47% reported ten years ago by Longo-Mbenza et al [20] in the same setting and by Kuate et al [21] at Douala in Cameroon, respectively. However, it is quite higher than that found by most other studies from sub-Saharan African countries [22]- [28]. The differences in the number of deaths between studies and countries could be explained by the differences in public health response against stroke, access to health services, treatment options, population studied, sample size and study design, statistical methods and threshold used to define hyperglycemia [24].…”
Section: Discussionmentioning
confidence: 74%